Classification Characteristics of Some Roads in Karbala City - Hayder S. Khudhair; Hamid Athab E. Al-Jameel; Vladimir N. Konoplev; Artur R. Asoyan (RUDN Journal of Engineering Research)
A comprehensive understanding of the characteristics of the road network is imperative for implementing fundamental measures to enhance traffic efficiency and mitigate delays. The objective of the present study is twofold: firstly, to classify the urban street network in the city of Karbala; and secondly, to evaluate its effectiveness. Following the delineation of the area of study, traffic data is collected through the utilisation of video imaging technology and subsequently extracted from video files. Following this, the city streets are divided into multiple sections, and the speed of movement in each is calculated, as well as the speed of free flow. The primary objective of this study is to determine and compare the level of service (LOS) of a road based on Highway Capacity Recommendations (HCM 2000), including traffic speed, capacity to assess each segment of the network. The findings of the study revealed that roads of the first category constituted 25% of the total, while roads of the second category comprised 75% of the total. Furthermore, the level of maintenance of street sections is 25% when working with LOS C, 31.25% when working with LOS D, 12.5% when working with LOS E and 31.25% when working with LOS F, according to the assessment of transport operations based on average traffic speed.